Diagnostic effectiveness of HIV-1 quantitative nucleic acid assay as a supplementary test for individuals with indeterminate or negative western blot antibody test results — China, 2018–2023 - Ding, Mengjun; Pan, Pinliang; Wang, Yu; Liu, Pei; Zhang, Xin; Zhu, Qiyu; Ding, Haifeng; Jin, Cong (BMC infectious diseases, 2025)
Background Based on China’s current HIV-1 testing algorithm, samples with initial positive antibody screening require two additional repeat tests, with infection status confirmed by HIV-1 antibody Western Blot or nucleic acid testing (NAT). In recent years, NAT has gradually become the mainstream supplemental assay due to its shorter window period, holding significant importance in detecting acute HIV-1 infection. Currently, over 800 laboratories in China can perform HIV-1 NAT. However, most NAT kits are designed for viral load (VL) detection, typically used to assess treatment efficacy in confirmed patients. This study aimed to explore the diagnostic efficacy of HIV-1 quantitative NAT at varying medical decision points, as well as the methodological preference for antibody screening, to support better implementation of HIV-1 testing and accurate identification of HIV-1 infections in China. Methods Testing records of 11,369 samples with WB-indeterminate or -negative results during 2018–2023 were collected from the central HIV confirmatory laboratory databases of 20 provincial CDCs. Methodological preferences in HIV-1 antibody screening, diagnostic performance of single- or double-reactive results in retesting and quantitative NAT at varying diagnostic thresholds were analyzed. Results Chemiluminescence immunoassay (CLIA) was the most widely used method for initial screening (42.77%) and the seroconversion rate was significantly higher in cases with double-positive retest results compared to single-positive results (75.95% vs. 27.25% for WB-indeteminate results and 20.31% vs. 7.26% for WB-negative results, respectively). The specificity and positive predictive values of HIV-1 quantitative NAT were 100% at each medical decision points, and the sensitivity and negative predictive value decreased from 99.92% to 99.93% to 94.71% and 95.64%. Two samples with undetectable viral loads were ultimately diagnosed as HIV-1 infections, alerting us to consider individual exposure history when managing antibody screening-reactive but VL-undetectable cases. Conclusions Quantitative HIV-1 NAT enables rapid and accurate infection confirmation, earlier identification and timely treatment initiation.